OP0057 The patients' knowledge about their disease: a french multicentric survey in ankylosing spondylitis (as). (1st June 2001) - Claudepierre, P; Flipo, RM; Sibilia, J; Berthelot, JM; Goupille, P; Cortinovis, S; Chevalier, X; Wendling, D
Abstract : Background: It is known that, in chronic diseases, patient education is a factor of good compliance and good disease management. An index was recently proposed to assess the level of knowledge in AS. 1 Objectives: To assess the level of knowledge of a population of AS patients from different tertiary care centres in France, and to identify some factors linked with this level. Methods: Study:multicentric cross-sectional study. No structured educational program was used in these centres at the time of the study. Patients: Inclusion criteria were New York criteria of AS and patients had to read French fluently. Data collected: demographic and sociocultural, disease characteristics, the index of knowledge in a French version (obtained from a double translation) giving a maximum score of 25. Statistical analysis: to seak a link between the knowledge score and collected factors, usual non parametric tests were used. Results: The mean score of the 95 included patients was only 16.4 (S. D. 4.8). The percentages of correct answers were not equally distributed among the 4 groups or domains of questions. The duration of disease management in a tertiary care centre appeared to be positively linked to the level of knowledge (r = 0.28 with p = 0.01, for the global score on 25 points, and r = 0.26 with p = 0.02, for the number of good answers (on 14) per patient). It was also observed that the level of knowledge was better in females than males, and in patients who have previously read on the disease or who knew the association of AS patients. No interaction was found between the factor "sex" or the factor "duration of disease management in a tertiary care centre" and the other identified factors, suggesting that they are independent factors associated with the level of knowledge. Conversely, the 3 other factors, e.g., level of education in 2 classes, previous reading, knowing of the association, were statistically linked two by two. The other tested factors were not significantly linked with the level of knowledge: age of the patients, duration of the disease, characteristics of the disease (axial or peripheral, psoriasis, radiological severity). Conclusion: The level of knowledge of these patients appears lower than this observed in the previous UK study, reinforcing the positive role of educational programs. These data will help to determine in which domains and in which patients the highest effort of education should be initially done. Reference: Lubrano E, et al . Br J Rheumatol. 1998;37:437–41